Maintaining Ethical Standards during Conservation Crises - Brook, Ryan K.; Cattet, Mark; Darimont, Chris T.; Paquet, Paul C.; Proulx, Gilbert (WBI Studies Repository, 2015)
Many species at risk in Canada and globally are at or approaching a crisis, especially where little or nothing consequential is being done to prevent extirpation. Such is the case of endangered boreal caribou (Rangifer tarandus caribou) in southern Alberta, Canada. Expedient but inadequate emergency ‘fixes’ have been experimentally implemented to arrest their decline and potential extirpation, but use of these measures raises important ethical problems. In their study of the effects of killing wolves (Canis lupus) on the Little Smoky woodland caribou population, Hervieux et al. (2014a) employed lethal methods that included shooting a firearm from a helicopter and the use of strychnine baits. Both of these methods raise critical questions with regard to animal welfare. When it is necessary to kill an animal, reliable humane procedures must be used to avoid pain or distress, and produce rapid loss of consciousness until death occurs. Also relevant are formal approvals by government and institutional animal ethics committees that adhere to Canadian Council on Animal Care (CCAC) guidelines. Shooting a moving animal from a helicopter is prone to error and not conducive to shots that quickly render animals insensitive to pain or produce a consistently quick kill. Strychnine does not meet the CCAC’s criteria for an acceptable killing method, and is specifically prohibited as an injectable option for euthanizing animals. Its use under uncontrolled conditions at bait sites is likely even less suitable. In addition, the risks of non-lethal and painful injuries from this poison and associated deaths to large numbers of non-target animals clearly contravene the CCAC guidelines for wildlife research. This study did not meet the CCAC’s guidelines and did not adhere to the Canadian Journal of Zoology’s requirement that all research must be approved by an institutional animal care committee. More broadly, and regardless of the failure of formal safeguards and implicit justifications offered by authors, we should be concerned ...